Is eating behavior manipulated by the gastrointestinal microbiota? Evolutionary pressures and potential mechanisms - Alcock, Joe; Maley, Carlo C.; Aktipis, C. Athena (BioEssays, 2014)
Microbes in the gastrointestinal tract are under selective pressure to manipulate host eating behavior to increase their fitness, sometimes at the expense of host fitness. Microbes may do this through two potential strategies: (i) generating cravings for foods that they specialize on or foods that suppress their competitors, or (ii) inducing dysphoria until we eat foods that enhance their fitness. We review several potential mechanisms for microbial control over eating behavior including microbial influence on reward and satiety pathways, production of toxins that alter mood, changes to receptors including taste receptors, and hijacking of the vagus nerve, the neural axis between the gut and the brain. We also review the evidence for alternative explanations for cravings and unhealthy eating behavior. Because microbiota are easily manipulatable by prebiotics, probiotics, antibiotics, fecal transplants, and dietary changes, altering our microbiota offers a tractable approach to otherwise intractable problems of obesity and unhealthy eating. Nutrient competition affects all biological communities, including the human microbiota. Selection favors microbes that can influence their nutrient supply, potentially leading to microbial manipulation of human feeding behavior. Manipulation may involve neurochemical rewards, toxins, vagus nerve modulation, and manipulation of taste receptors, leading to cravings and unhealthy eating behavior.